Performance measurement : a case study in ABC company - Cai, Shilin (2008)
The business world is changing to a more dynamic and uncertain one. Performance measurement has been recognized as a key issue in enhancing business performance. In this study, we seek to explore the performance measurement system in the insurance industry. This will be illustrated through the case study of a renowned life insurance company.